2014
DOI: 10.3892/mmr.2014.2837
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of microRNA expression in Parkinson’s disease

Abstract: Abstract. Parkinson's disease (PD) is a type of movement disorder caused by loss of dopamine-producing neurons in the midbrain. In order to identify the synergistic microRNA (miRNA) pattern in PD, miRNA and mRNA double expression profiles of PD were downloaded. Differentially expressed miRNA and mRNA were identified [P<0.01, following false discovery rate (FDR) correction]. A cumulative hypergeometric distribution test was then performed to identify synergistic miRNAs (P<0.01, following FDR correction). Gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Recent work has emphasised the association of selected microRNAs to PD [27,122,123] and roles for microRNAs in neuroinflammation have received increased attention [25,124]. As neuroinflammation is thought to be a facilitator of PD pathogenesis, and was observed in the pre-motor PD model used in this study [32,125], we assessed changes in relative expression levels of three inflammatory and hypoxia associated microRNAs: miR21, miR155, and miR210.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has emphasised the association of selected microRNAs to PD [27,122,123] and roles for microRNAs in neuroinflammation have received increased attention [25,124]. As neuroinflammation is thought to be a facilitator of PD pathogenesis, and was observed in the pre-motor PD model used in this study [32,125], we assessed changes in relative expression levels of three inflammatory and hypoxia associated microRNAs: miR21, miR155, and miR210.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been identified to be abnormally expressed in the brain tissues of patients or animals with PD and are responsible for the development of DA neurons [12,2628]. Thus, many miRNAs are regarded as novel biomarkers for molecular diagnosis and potential therapy targets.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, endogenous, noncoding RNA molecules, which have exhibited potential as biomarkers or therapeutic targets for PD ( 11 13 ). Bioinformatics analysis has revealed that ~200 miRNAs, including miR-627, miR-634, miR-514, miR-563 and miR-613, are differentially expressed between PD and healthy tissue samples ( 14 ), suggesting that miRNAs may participate in PD pathogenesis and progression. In addition, upregulation of miR-124 has been demonstrated to regulate autophagy and apoptotic processes, and thus reduce the loss of DAergic neurons in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced model of PD ( 15 ).…”
Section: Introductionmentioning
confidence: 99%